Negotiating The Authority of Female Ulama in the Reinterpretation of the Qur'an in Islamic Family Law in East Kalimantan - Zainuddin, Iskandar; Thobroni, Ahmad Yusam; Ridha Rosyadi, Muhammad Arief; Lahmuddin, Fakhruddin; Qardlawi, Muhammad Yusuf (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2026)
The debate over authority in contemporary Quranic interpretation surrounding Islamic family law remains a frequent issue, particularly for female ulama. This article examines how female ulama in East Kalimantan negotiate religious authority through Quranic reinterpretation to transform the understanding and practice of Islamic family law. Using a convergent mixed-methods design, this study combines quantitative analysis of 30 purposively selected female ulama in five districts/cities. Then, qualitative methods derived from in-depth interviews with experts in Islamic interpretation and family law are analyzed using the theory of maqāṣid al-sharīʿah. The research findings reveal that 86.7% of participants actively engage in progressive reinterpretation of Quranic texts related to crucial issues of family law, including dowry, divorce (khulʿ), child custody (ḥaḍānah), and joint property. Statistical analysis shows a significant correlation (p < 0.05) between a hybrid educational background integrating Islamic boarding school education with modern Islamic higher education and a stronger tendency to challenge conventional interpretive paradigms. Quranic interpretation functions not merely as a theological practice but also as a process of negotiating religious authority through contextual reasoning, maqāṣid al-sharīʿah, and intertextual hermeneutics. This article contributes to the body of scholarship on Islamic feminism, religious authority, and legal pluralism in Indonesia, while also highlighting grassroots dynamics in Islamic family law reform.